2018
DOI: 10.1002/ame2.12002
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox genes for embryo implantation: From mouse to human

Abstract: The proper development of uterus to a state of receptivity and the attainment of implantation competency for blastocyst are 2 indispensable aspects for implantation, which is considered to be a critical event for successful pregnancy. Like many developmental processes, a large number of transcription factors, such as homeobox genes, have been shown to orchestrate this complicated but highly organized physiological process during implantation. In this review, we focus on progress in studies Homeobox genes are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 100 publications
0
18
0
Order By: Relevance
“…In recent years, the incidence of uterine disease in dairy cows has shown an increasing trend, and has become one of the most important factors affecting their reproductive efficiency ( 1 ). The endometrium plays an essential role in embryo implantation, embryo development, and sperm motility ( 2 ). Endometritis is a type of refractory uterine disease, which is mainly caused by pathogenic microorganisms (such as Escherichia coli and Streptococcus ) infecting the endometrium during or after parturition ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the incidence of uterine disease in dairy cows has shown an increasing trend, and has become one of the most important factors affecting their reproductive efficiency ( 1 ). The endometrium plays an essential role in embryo implantation, embryo development, and sperm motility ( 2 ). Endometritis is a type of refractory uterine disease, which is mainly caused by pathogenic microorganisms (such as Escherichia coli and Streptococcus ) infecting the endometrium during or after parturition ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cermik et al have shown that HOXA10 is involved in the regulation of progesterone's transcription targets and in the regulation of endometrial receptivity. The reduction of HOXA10 expression in the uterus might be one of the important reasons for progesterone resistance, poor endometrial receptivity, and reduced reproductive potential in patients with PCOS (He et al, 2018). In summary, progesterone resistance is an important mechanism leading to poor endometrial receptivity, endometrial dysplasia, and even endometrial cancer in patients with PCOS.…”
Section: )mentioning
confidence: 98%
“…Correspondingly, women with infertility exhibit a significantly reduced expression of ERb (69,70). In addition to nuclear receptor transcription factors, such as ER and PR, studies on knockout mice have shown that multiple transcription factors, including Hox family transcription factors, Msx transcription factors, and Kruppel-like transcription factors, also regulate uterine receptivity (71)(72)(73)(74)(75)(76)(77)(78). In the reproductive system, Hox genes are known to be widely involved in the development of mouse and human reproductive systems, and consequently in the maintenance of early pregnancy.…”
Section: Potential Factors Affecting Endometrial Functionmentioning
confidence: 99%